Perbedaan Konsentrasi Kitosan Terhadaptingkat Kesukaan dan Daya Simpan Tahu - Manurung, Januari; Efendian, Raswen; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposeof this studyistodeterminethe exactconcentration ofchitosanonorganoleptic qualityandstorabilityknow. The research wasdoneexperimentallybyusingCompletely Randomized Design(CRD) nonfactorialconsistingof 4treatments and 4replications. Thetreatmentinthispeneletinis: K0=Withoutthe addition ofchitosanconcentration(0%), K1=Addition of1% chitosanconcentrationofstock solution, K2=Addition of2% chitosanconcentrationofstock solutionandK3=Addition of3% chitosanconcentrationofstock solution.The data obtainedwere statistically analyzedusinganalysisof variance(ANOVA), followed by Duncan's testNewMultiple RangeTest(DNMRT) atthe level of 5%. The best treatmentattheintensive searchwasoutwiththe addition of2% chitosanconcentrationwithpH, totalbacteria, protein content andassessmentrequirementsorganeleptikaccordancewithSNI01-3142-1998andcanextend the shelf life. Keyword :Chitosan, shelf life, Tofu